THU0006 Trans-ethnic meta-analysis of genome-wide association studies identifies GSDMA and PRDM1 as susceptibility genes to systemic sclerosis. (15th June 2017) - Terao, C; Kawaguchi, T; Dieude, P; Varga, J; Kuwana, M; Hudson, M; Kawaguchi, Y; Matucci-Cerinic, M; Ohmura, K; Riemekasten, G; Kawasaki, A; Airo, P; et al.
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune disease characterized by fibrosis and composed of two subtypes, limited and diffuse cutaneous forms. Previous genetic studies including genome-wide association studies (GWAS) have identified 12 susceptibility loci satisfying genome-wide significance. Objectives: To expand the list of susceptibility genes and deepen biological insights for SSc. Methods: We performed trans-ethnic meta-analysis of GWAS in the Japanese and European populations, followed by a two-staged replication study comprising a total of 4, 436 cases and 14, 751 controls. Associations between significant single nuclear polymorphisms (SNPs) and neighboring genes were evaluated. Enrichment analysis of H3K4Me3, a representative histone mark for active promoter was conducted with an expanded list of SSc susceptibility genes. Results: We identified two significant SNP in two loci, GSDMA and PRDM1, both of which are related with immune functions and associated with other autoimmune diseases (p=1.4x10 -10 and 6.6x10 -10, respectively). GSDMA also showed a significant association with limited cutaneous SSc. We also replicated the associations of previously reported loci including a non-GWAS locus, TNFAIP3 . PRDM1 encodes BLIMP1, a transcription factor regulating T cell proliferation and plasma cell differentiation. The top SNP in GSDMA was a missense variant and correlated with gene expression of neighboring genes, and this could explain the association in this locus. We found different HLA association patterns between the two populations or two subtypes. Enrichment analysis suggested the importance of CD4 naïve primary T cell. Conclusions: GSDMA and PRDM1 are associated with SSc. These findings provide enhanced insight into the genetic and biological basis of SSc. Disclosure of Interest: None declared